THE SCIENTIFIC ACTIVITY OF Y.E.BERTELS IS AN ORIENTALIST (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
In this article, East people’s history ,culture, language of the greatspecialist Y.E.Bertels life and work ,essence of his scientific activity are revealed.Atthe same time, the article talks about the contribution of the great thinker Jami’sscientific heritage of learning